42 Identification of an inherent mechanism of NADPH oxidase signalling in doxorubicin cardiotoxicity. Issue 20 (23rd September 2011) - McLaughlin, D; McKeag, P; Doherty, K; McVicar, C; Grieve, D J; McDermott, B J
Abstract : Anthracyclines used in cancer therapeutics, including doxorubicin (DOX), cause both short- and long-term cardiotoxicity associated with increased myocardial oxidative stress. Chronic DOX treatment increases superoxide anion production in vivo, which is derived largely from Nox2 NADPH oxidase and contributes to key processes underlying cardiac dysfunction. The aim of this study was to identify possible mechanisms involved in the signal relay from increased Nox2 activity to development of disease phenotype. In this context, we performed a whole-genome gene expression array (Illumina MouseWG-6 v2.0) of ventricular tissue from DOX-treated wild type vs Nox2KO mice. Pathway analysis (GeneGo Metacore) revealed the apoptotic process most significant to the data set (p=0.00005). Applying the 63 relevant genes (FDR cut-off, adjusted p<0.05) in a network analysis showed significant mRNA increases in peroxisome proliferator-activated receptor-γ coactivator 1α (PGC-1α) and the mitochondrial membrane protein, mitofusin-2, known to be upregulated by PGC-1α. Since mitofusin-2 independent of its pro-fusion effect can form a functional unit with the Bcl-2 family member, Bax, the potential involvement of mitofusin-2 in DOX-mediated apoptosis was investigated. In HL-1 cardiomyocytes, superoxide production was significantly increased by 13±3% by DOX (10–7M; 3 h) and H2O2 generated increases of 66%±22% and 44%±17% (10–7M; 3 h, 20 h) along with marked upregulation of Nox2 mRNA at 3 h (2.9-fold). DOX increased caspase 3/7 activity 3.0-fold at 20 h. In a similar time frame, DOX increased mitofusin-2 mRNA at 3 h and protein at 24 h. NOX2-mediated upregulation of mitofusin-2 and its pleiotropic effect on apoptosis may play a part in DOX-associated cardiomyocyte dysfunction.